Composite structures for civil and architectural engineering - Kim, D.-H. (E & FN Spon, 1995)
Introduction; Properties of composites; Classical theory of elasticity and mechanics; Eigenvalue problems of beams and frames of isotropic materials; Anisotropic; One-dimensional structural elements of composite materials; Plates and panels of composite materials; Failure of composites; Joints; Design.